Praktek Akad Qardhul Hasan Pada Bank Wakaf Mikro - Ani Faujiah (ACTIVA: Jurnal Ekonomi Syariah, 2020)
Absract : Improvement of community welfare is carried out by Islamic financial institutions by providing benevolent funds and conducting social responsibility programs. The benevolent fund or Qardhul hasan contract in the Islamic Financial Institution is known as a loan fund agreement to the customer provided that the customer is obliged to return the loan principal received at the agreed time both at once and in installments. Qardhul Hasan financing procedures implemented in Islamic Financial Institutions and how the distribution of Qardhul Hasan financing in Islamic Financial Institutions, aims to perfect the obligations of relationship with God, relations with humans and relations with the natural surroundings in order to produce economic development in order to improve the quality of life better. By using quantitative methods through techniques of analysis, observation and documentation to obtain a conclusion. In general, the source of funding for Qardhul Hasan is through Zakat, Infaq, Shodaqoh from LAZNAS (National Amil Zakat Institution) in Islamic Financial Institutions. The distribution of Qardhul Hasan financing in Islamic Financial Institutions has been carried out on target, namely that those who receive Qardhul Hasan financing are only the middle to lower class who have Small and Medium Enterprises (SMEs) because they have conducted a survey of the actual condition of their customers, this Qardhul Hasan financing is appropriate with the Qardh contract, which is that this financing is intended to be social and please help, and the customer is only required to return the principal without the margin. Money Waqf can help the development of Islamic banks, especially Islamic Rural Banks. The advantages of waqaf funds, besides being eternal or long-term, waqaf funds are the cheapest funds that should be the target of Islamic banks (micro waqf bank). Key words: Funding, Qardhul hasan and micro waqf bank Abrstrak Peningkatan kesejahteraan masyarakat dilakukan oleh lembaga keuangan syariah dengan memberikan pembiayaan dana kebajikan dan melakukan program tanggung jawab sosial. Dana kebajikan atau akad Qardhul hasan dalam Lembaga Keuangan Syariah dikenal dengan akad pinjaman dana kepada nasabah dengan ketentuan bahwa nasabah wajib mengembalikan pokok pinjaman yang diterimanya pada waktu yang telah disepakati baik secara sekaligus maupun cicilan. Prosedur pembiayaan Qardhul Hasan yang diterapkan di Lembaga Keuangan Syariah serta bagaimana penyaluran pembiayaan Qardhul Hasan di Lembaga Keuangan Syariah, bertujuan untuk menyempurnakan kewajiban hubungan dengan Allah SWT, hubungan dengan manusia dan hubungan dengan alam sekitar dalam rangka menghasilkan pembangunan ekonomi guna meningkatkan kualitas kehidupan yang lebih baik. Dengan menggunakan metode Kuantitatif melalui teknik analisis, observasi dan dokumentasi untuk memperoleh sebuah kesimpulan. Pada umumnya sumber dana pembiayaan Qardhul Hasanmelalui Zakat, Infaq, Shodaqoh yang berasal dari LAZNAS (Lembaga Amil Zakat Nasional) di Lembaga Keuangan Syariah. Penyaluran pembiayaan Qardhul Hasan di Lembaga Keuangan Syariah sudah terlaksana dengan tepat sasaran yaitu pihak yang mendapat pembiayaan Qardhul Hasan ini hanya masyarakat menengah kebawah yang memiliki Usaha Kecil dan Menengah (UKM) kerena dilakukan survei terlebih dahulu mengenai keadaan nasabah sebenarnya, pembiayaan Qardhul Hasan ini sudah sesuai dengan akad Qardh yaitu pembiayaan ini ditunjukan untuk sosial dan tolong menolong serta nasabah hanya wajib mengembalikan pokok pembiayaannya saja tanpa dikenai margin waqaf uang dapat membantu perkembangan bank-bank syariah, khususnya BPR Syariah. Keunggulan dana waqaf, selain bersifat abadi atau jangka panjang, dana waqaf adalah dana termurah yang seharusnya menjadi incaran bank-bank Syariah(bank wakaf mikro) Kata Kunci : Pembiayaan, Qardhul hasan dan bank wakaf mikro